Cinema e lembranças : O documentário Dzi Croquettes (2009) e a construção de biografias e legados (TEL Tempo, Espaço e Linguagem, 2021)
This paper aims to analyse and apprehend the role of the cinematographic narrative present in the documentary Dzi Croquettes (2009), directed by Tatiana Issa and Raphael Alvarez, as a element of research of the biographies of Lennie Dale, the “father” of the group, and Wagner Ribeiro, the “mother”, and their legacies on the Brazilian theater, arts and music. Thus, through the understanding of their trajectories, before or after their involvement in the group, we want to know how their lifes are built and explored, we aim to analyse simultaneously how the documentary monumentalize this past.